Attitudes of Physicians toward Palliative Care in Intensive Care Units: A Nationwide Cross-Sectional Survey in Japan - Tanaka, Yuta; Kato, Akane; Ito, Kaori; Igarashi, Yuko; Kinoshita, Satomi; Kizawa, Yoshiyuki; Miyashita, Mitsunori (Journal of pain and symptom management, 2022)
Palliative care is an essential component of comprehensive care for patients with critical illnesses. In Japan, little is known about palliative care in intensive care units (ICUs), and palliative care approaches are not widespread. This study aimed to better understand the attitudes of physicians toward palliative care and the utilization and needs of specialized palliative care consultations in ICUs in Japan. A nationwide, self-administered questionnaire was distributed ICU physician directors in all hospitals with ICUs. Questionnaires were distributed to 873 ICU physician directors; valid responses were received from 436 ICU physician director (50% response rate). Among the respondents, 94% (n = 411) felt that primary palliative care should be strengthened in ICUs; 89% (n = 386) wanted ICU physicians to collaborate with specialists, such as palliative care teams (PCTs); and 71% (n = 311) indicated the need for specialized palliative care consultations; however, only 38% (n = 166) actually consulted, and only 6% (n = 28) consulted more than 10 patients in the past year. Physicians most commonly consulted PCT for patients with serious end-of-life illness (24%) (n = 107), intractable pain (21%) (n = 92), and providing psychological support to family members (43%, n = 187). The potential barriers in providing primary and specialized palliative care included being unable to understand the patients’ intentions (54%, n = 235), lack of knowledge and skills in palliative care (53%, n = 230), and inability to consult with PCTs in a timely manner (46%, n = 201). These data suggest a need for primary palliative care education in ICUs and improved access to specialized palliative care consultations.